Identification of HNPCC by Molecular Analysis of Colorectal and Endometrial Tumors. Issue 4 (21st May 2013) - Vasen, H. F. A.; Hendriks, Y.; de Jong, A. E.; van Puijenbroek, M.; Tops, C.; Bröcker-Vriends, A. H. J. T.; Wijnen, J. Th.; Morreau, H.
Abstract : Hereditary nonpolyposis colorectal cancer (HNPCC, Lynch syndrome) is a dominantly inherited syndrome characterized by the development of colorectal cancer, endometrial cancer and other cancers and the presence of microsatellite instability (MSI) in tumors. The Bethesda guidelines have been proposed for the identification of families suspected of HNPCC that require further molecular analysis. We have evaluated the yield of MSI-analysis in a large series of Dutch families suspected of HNPCC. We also analysed whether the loss of mismatch repair (MMR) protein detected by immunohistochemistry (IHC) of colorectal cancer (CRC) and endometrial cancer correlated with the presence of MSI and/or a MMR gene mutation. The results showed that the Bethesda criteria with a few modifications are appropriate to identify families eligible for genetic testing. In addition, we found that MSI and IHC-analysis of CRC using antibodies against MLH1, MSH2, MSH6 and PMS2 proteins are equally effective for identifying carriers of the known MMR gene defects. However, as long as the role of other putative MMR genes in hereditary CRC has not been elucidated, IHC-analysis cannot completely replace MSI. For this reason, we prefer MSI-analysis as first step in families suspected of HNPCC. On the other hand, in families fulfilling the revised Amsterdam criteria in which the probability of detecting a mutation is relatively high, we would recommend IHC as first diagnostic step because the result might predict the specific underlying MMR gene mutation. MSI or IHC-analysis of endometrial cancer alone was found to be less sensitive compared with these tests performed in colorectal cancer. Therefore, probably the best approach in the analysis of this cancer is to perform both techniques. The identification of HNPCC is important as it makes it possible to target effective preventative measures. Our studies showed that MSI and IHC analysis of colorectal and endometrial cancer, are reliable cost-effective tools that can be used to identify patients with HNPCC.